Cardiovascular Responses to Commonly Used Tests In and Outside of the Laboratory Settings - Dikshit, Mohan B. (Annals of the National Academy of Medical Sciences (India), 2022)
Several tests are available for assessing cardiovascular response to various interventions which may be given in the laboratory, or outside of it in the field. The tests are meant to excite or deactivate cardiovascular and other sensory receptors which signal the central mechanisms. They have been found useful in generating data to study cardiovascular effects on subjects exposed to specialized physical training (e.g., athletes), in the evaluation of people engaged in special occupations such as pilots, astronauts, and other military personnel, and in training undergraduate and postgraduate students. If the response does not fit into the physiological norm, it may reflect a temporary aberration, or a more serious defect in the cardiovascular control mechanism because of disease. Interpretation of data generated may vary between various operators/observers. Here, an attempt has been made to bring out responses of the cardiovascular system to the commonly used tests, and their applicability in clinical situations.
Keywords: cardiovascular system responses; central blood volume; cold pressor test; lower body negative pressure; exercise response